2007
DOI: 10.1016/j.ijdevneu.2007.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal hypoxia down regulates the GABA pathway in newborn mice cerebral cortex; partial protection by MgSO4

Abstract: The fetal and newborn brain is particularly susceptible to hypoxia, which increases the risk for neurodevelopmental deficits, seizures, epilepsy and life-span motor, behavioral and cognitive disabilities. Here, we report that prenatal hypoxia at gestation day 17 in mice caused an immediate decrease in fetal cerebral cortex levels of glutamate decarboxylase, a key proteins in the GABA pathway. While maternal MgSO4 treatment prior to hypoxia did not have an early effect, it did accelerate maturation at a later s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 35 publications
(50 reference statements)
2
25
0
Order By: Relevance
“…PCR analyses were conducted in the cerebral cortex with gene-specific primers and fluorescently labeled Taq probe GAD1 (Rn 00690304_g1) Neurochem Res (2012) 37:629-638 635 which can be correlated to the decreased GABA receptors in the straitum. Neonatal hypoxia in wistar rats and prenatal hypoxia at gestation day 17 in mice was reported to decrease fetal cerebral cortex expression and levels of GAD [30,31]. Decreased levels of key proteins in the GABA pathway may lead to high susceptibility to seizures and epilepsy in newborns after prenatal or perinatal hypoxia [26].…”
Section: Discussionmentioning
confidence: 99%
“…PCR analyses were conducted in the cerebral cortex with gene-specific primers and fluorescently labeled Taq probe GAD1 (Rn 00690304_g1) Neurochem Res (2012) 37:629-638 635 which can be correlated to the decreased GABA receptors in the straitum. Neonatal hypoxia in wistar rats and prenatal hypoxia at gestation day 17 in mice was reported to decrease fetal cerebral cortex expression and levels of GAD [30,31]. Decreased levels of key proteins in the GABA pathway may lead to high susceptibility to seizures and epilepsy in newborns after prenatal or perinatal hypoxia [26].…”
Section: Discussionmentioning
confidence: 99%
“…Literature data demonstrate that prenatal hypoxia can selectively cause disruption of various mediator systems in postnatal ontogenesis [42,64,65]. Using a vesicular acetylcholine transporter (VAChT) as a marker protein we have found that, in adult rats subjected to prenatal hypoxia on Е14, the number of VAChT-positive cholinergic terminals, which form synapses on the bodies of the pyramidal neurons in the V-VI layers of the parietal cortex is decreased compared to control …”
Section: Impairment Of Chemical Neuronal Interactionsmentioning
confidence: 97%
“…Hypoxia might regulate cell proliferation by altering the fetal cerebella gene expression, which is evidenced by a trend of upregulation in cell cycle-related genes seen 2 h after fetal hypoxia, followed by downregulation 24 h or 20 days after hypoxia [18]. In addition, key proteins in the gamma-aminobutyric acid (GABA) pathway were immediate repressed by transient hypoxia in the fetal cerebral cortex, which might result in an increased susceptibility to seizures and epilepsy in the offspring [17]. It is possible that hypoxia-induced fetal programming in the brain development is responsible for the increased vulnerability to cerebral insults in adulthood [58].…”
Section: Fetal Hypoxia and Abnormal Heart And Brain Developmentmentioning
confidence: 99%
“…Fetal hypoxia also increases the risk of heart failure and other cardiovascular disease in later postnatal life [16]. In addition to the adverse effect on heart development, numerous studies have demonstrated that fetal hypoxia is one of the major causes of neurodevelopmental impairment and neurological deficits in the offspring [1722]. …”
mentioning
confidence: 99%